2023
DOI: 10.1177/10497315231189177
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health Interventions for Incarcerated Adults With Histories of Trauma: A Scoping Review

Melissa D. Grady,
Stephen Tripodi,
Lauren Herod
et al.

Abstract: Purpose: The majority of incarcerated individuals have experienced traumatic events in their lifetime, contributing to related behavioral health issues, including post-traumatic stress, mood, anxiety, and substance use disorders. The purpose of this article is to understand the existing state of the literature through a scoping review on correctional-based programs that address both trauma and behavioral health. Methods: Proquest and EBSCO databases were searched to identify studies focused on trauma and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…A systematic review found that over 50% of Black men who experienced trauma may have unmet treatment needs (Motley & Banks, 2018). Despite the high rates of trauma among men involved in the legal system, there has also been a recent call for more interventions and related research on trauma for men who are incarcerated, a population noted to be “significantly underserved” (Grady et al, 2023, p. 14). The results from this study highlight the potential importance of and need for interventions for newly released Black SMM with PTSD symptoms—a population that may be at a heightened risk for contracting STIs.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that over 50% of Black men who experienced trauma may have unmet treatment needs (Motley & Banks, 2018). Despite the high rates of trauma among men involved in the legal system, there has also been a recent call for more interventions and related research on trauma for men who are incarcerated, a population noted to be “significantly underserved” (Grady et al, 2023, p. 14). The results from this study highlight the potential importance of and need for interventions for newly released Black SMM with PTSD symptoms—a population that may be at a heightened risk for contracting STIs.…”
Section: Discussionmentioning
confidence: 99%